Estimating the Impact of Carbon Dioxide Absorbent Performance Differences on Absorbent Cost During Low-Flow Anesthesia. (February 2020) - Feldman, Jeffrey M.; Lo, Christopher; Hendrickx, Jan
Abstract : BACKGROUND: Reducing fresh gas flow when using a circle anesthesia circuit is the most effective strategy for reducing both inhaled anesthetic vapor cost and waste. As fresh gas flow is reduced, the amount of exhaled gas rebreathed increases, but the utilization of carbon dioxide absorbent increases as well. Reducing fresh gas flow may not make economic sense if the increased cost of absorbent utilization exceeds the reduced cost of anesthetic vapor. The primary objective of this study was to determine the minimum fresh gas flow at which absorbent costs do not exceed vapor savings. Another objective is to provide a qualitative insight into the factors that influence absorbent performance as fresh gas flow is reduced. METHODS: A mathematical model was developed to compare the vapor savings with the cost of carbon dioxide absorbent as a function of fresh gas flow. Parameters of the model include patient size, unit cost of vapor and carbon dioxide absorbent, and absorbent capacity and efficiency. Boundaries for fresh gas flow were based on oxygen consumption or a closed-circuit condition at the low end and minute ventilation to approximate an open-circuit condition at the high end. Carbon dioxide production was estimated from oxygen consumption assuming a respiratory quotient of 0.8. RESULTS: For desflurane, the cost of carbon dioxide absorbent did not exceed vapor savings until fresh gas flow was almost equal to closed-circuit conditions. For sevoflurane, as fresh gas flow is reduced, absorbent costs increase more slowly than vapor costs decrease so that total costs are still minimized for a closed circuit. Due to the low cost of isoflurane, even with the most effective absorbent, the rate of absorbent costs increase more rapidly than vapor savings as fresh gas flow is reduced, so that an open circuit is least expensive. The total cost of vapor and absorbent is still lowest for isoflurane when compared with the other agents. CONCLUSIONS: The relative costs of anesthetic vapor and carbon dioxide absorbent as fresh gas flow is reduced are dependent on choice of anesthetic vapor and performance of the carbon dioxide absorbent. Absorbent performance is determined by the product selected and strategy for replacement. Clinicians can maximize the performance of absorbents by replacing them based on the appearance of inspired carbon dioxide rather than the indicator. Even though absorbent costs exceed vapor savings as fresh gas flow is reduced, isoflurane is still the lowest cost choice for the environmentally sound practice of closed-circuit anesthesia.